O Brasil imaginado por candidatos à presidência: uma abordagem sistêmico-funcional do discurso eleitoral - Schmidt, Ana Paula Carvalho (2021)
A diachronic analysis of electoral political discourse contributes to reveal the issues emphasized and neglected by parties. Our aim is to identify, compare, and synthesize lexicogrammatical and semantic resources used for constructing imaginaries by elected candidates to the Brazilian presidency from 1989 to 2018. Both the linguistic and semantic parameters analysis (LI; LUI; FUNG, 2020) are based on Systemic Functional Linguistics theory (HALLIDAY, 2014). The process of data generation consisted of gathering samples of oral (transcription of 5 televised interviews), and written (8 party manifestoes) electoral texts produced by presidential candidates who were elected from 1989 to 2018. A qualitative approach in combination with quantitative tools was used (SARDINHA, 2004; SCOTT, 2020) to analyse and explain linguistic data in two stages. First, we focused on each party manifesto and interview departing from the lexicogrammatical stratum to identify the main issues that guided their campaign proposals as well as its linguistic realization. Based on linguistic evidence, we describe the text’s context of production and their register variables. At the lexicogrammatical stratum, attributive relational clauses constructed imaginaries most frequently. The candidates made use of Epithets such as “indispensable”, “imperative”, and “necessary” to express the degree of obligatoriness and necessity that a proposal become reality through the acting of voters in their favor. In regards to linguistic forms (irrealis function) for the realization of imaginaries, it occurred mainly in the process, in verbal groups temporally marked by the future tense or the subjunctive mood. Other forms of realization were in the Attribute or through modulation. The results of the contextual and semantic parameters analysis indicate that electoral imaginaries in relational clauses prioritized the Economic topic in the manifestoes, except in Roussef’s document, which emphasized the Welfare State issue. In the interviews, Collor, Cardoso and Lula approached the Political System category most frequently, whereas Rousseff and Bolsonaro focused on Economy and Social Groups respectively.